2007
DOI: 10.1158/1055-9965.epi-06-1047
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends in Mammographic Percent Density and Breast Cancer Risk

Abstract: Background: Mammographic density is a strong risk factor for breast cancer. However, whether changes in mammographic density are associated with risk remains unclear. Materials and Methods: A study of 372 incident breast cancer cases and 713 matched controls was conducted within the Mayo Clinic mammography screening practice. Controls were matched on age, exam date, residence, menopause, interval between, and number of mammograms. All serial craniocaudal mammograms 10 years before ascertainment were digitized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
112
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 36 publications
(44 reference statements)
7
112
1
Order By: Relevance
“…Two longitudinal studies have examined the relationship between change in density and breast cancer risk, one over an average of 4 -5 years (Maskarinec et al, 2006) and the other over an average of 7 years (Vachon et al, 2007a). Both used computer-assisted quantitative measurement of mammographic density and both showed that change in density with time was similar in women who developed breast cancer and those who remained free of disease (an example is shown in Figure 1B), but that at all ages, density was more extensive in women who develop breast cancer.…”
Section: Mammographic Density Involution and 'Breast Tissue Age'mentioning
confidence: 99%
See 2 more Smart Citations
“…Two longitudinal studies have examined the relationship between change in density and breast cancer risk, one over an average of 4 -5 years (Maskarinec et al, 2006) and the other over an average of 7 years (Vachon et al, 2007a). Both used computer-assisted quantitative measurement of mammographic density and both showed that change in density with time was similar in women who developed breast cancer and those who remained free of disease (an example is shown in Figure 1B), but that at all ages, density was more extensive in women who develop breast cancer.…”
Section: Mammographic Density Involution and 'Breast Tissue Age'mentioning
confidence: 99%
“…With the exception of the study of Kerlikowske, the available evidence suggests that it is the extent of density at a given age, rather than the rate of change of density with increasing age, that is related to breast cancer risk (Maskarinec et al, 2006;Vachon et al, 2007a). However, there are important gaps in knowledge concerning cumulative exposure.…”
Section: Mammographic Density Involution and 'Breast Tissue Age'mentioning
confidence: 99%
See 1 more Smart Citation
“…In the former situation, clinical breast exam may find tumors which are not detected in mammography (Drukteinis et al, 2013). Moreover, high density breasts in mammography are at a higher risk for breast cancer (McCormack and dos Santos Silva, 2006;Vachon et al, 2007;Heine et al, 2008;Zulfiqar et al, 2011;Phipps et al, 2012). When using breast density as a predictor of breast cancer risk, the majority of the studies report 2-to 6-fold increased risks for the highest group in comparison with the lowest risk categories (McCormack and dos Santos Silva, 2006;Vachon et al, 2007;Galukande and Kiguli-Malwadde, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high density breasts in mammography are at a higher risk for breast cancer (McCormack and dos Santos Silva, 2006;Vachon et al, 2007;Heine et al, 2008;Zulfiqar et al, 2011;Phipps et al, 2012). When using breast density as a predictor of breast cancer risk, the majority of the studies report 2-to 6-fold increased risks for the highest group in comparison with the lowest risk categories (McCormack and dos Santos Silva, 2006;Vachon et al, 2007;Galukande and Kiguli-Malwadde, 2012). Density in mammography has been accepted as one of the strongest risk factor for the cancer (Hanna and Diorio, 2013), stronger than nulliparity and early menarche, implying some independency to estrogen mediated effects in its carcinogenesis (Galukande and Kiguli-Malwadde, 2012).…”
Section: Discussionmentioning
confidence: 99%